Assessment of the atrial electromechanical properties of patients with human immunodeficiency virus. Issue 6 (November 2017) - Ertem, Ahmet G.; Yayla, Çağrı; Açar, Burak; Ünal, Sefa; Erdol, Mehmet A.; Sonmezer, Meliha Ç.; Kaya Kiliç, Esra; Ataman Hatipoglu, Çiğdem; Gokaslan, Serkan; Kafes, Habibe; Akboga, Mehmet K.; Aladag, Pelin; et al.
Abstract: The relationship between atrial fibrillation and human immunodeficiency virus (HIV) infection was evaluated. Electro-echocardiographic methods can be used to predict the development of atrial fibrillation (AF). In this study, we aimed to investigate the atrial electromechanical delay (AEMD) parameters of HIV (+) patients. Forty-two HIV (+) patients and 40 HIV (−) healthy volunteers were prospectively enrolled in this study. The electromechanical properties of the subjects' atria were evaluated with tissue Doppler imaging. The left-AEMD, right-AEMD and inter-AEMD were increased in the HIV (+) patients relative to the controls (p = 0.003, p < 0.001, and p < 0.001, respectively). The CD4 count was inversely correlated with the inter-AEMD (r = −0.428, p < 0.001). The CD4 count was an independent predictor of the inter-AEMD ( β  = 0.523, p = 0.007). Our study demonstrated that both the inter- and intra-atrial electromechanical delays were prolonged in the patients with HIV. This non-invasive and simple technique may provide significant contributions to the assessment of the risk of atrial arrhythmia in patients with HIV.